Significant influence of low positive affect on pain: impact of COVID-19 on affect and daily chronic non-cancer pain trajectories in women - Kuper, Quinte T. Y.; Waardenburg, Sophie F.; Visseren, Lars; Jongen, Ellen M. M.; Lousberg, Richel; van Amelsvoort, Therese A. M. J.; Balthasar, Andrea J. R. (Frontiers in Pain Research, 2025)
ObjectiveChronic non-cancer pain (CNCP) affects 12% of the Dutch population, with similar rates in other Western countries. CNCP not only influences the physical aspects of the body but also has a relationship with affect. Affect can be positive (PA) or negative (NA). This study investigated the relationship between pain and affect and how this relationship may have differed before and during the coronavirus disease 2019 (COVID-19) pandemic.MethodsIn this prospective study, patients were recruited during a standard pre-consultation visit at an outpatient pain clinic. The novelty of this approach lies in the utilisation of the experience sampling method (ESM). Patients were asked to complete an ESM digital tool 10 times a day for six consecutive days. They were categorised into the pre-COVID-19 (before March 20, 2020; n = 14) and during-COVID-19 (after March 20, 2020; n = 11) groups. The study cohort consisted of females only.ResultsPatient pain levels, NA, and PA were assessed. Patients with a low PA during the pandemic experienced a significant negative impact on their daily pain levels, correlating with a 2.7-point increase on a 0–10 numeric rating scale.ConclusionsUnlike the previous focus on the effect of high NA on pain, this study emphasises the negative influence of low PA, which can likely be attributed to reduced hedonic activities during global life events, such as the COVID-19 pandemic. Understanding the micro-level impact of low PA on individuals may provide novel targeted treatment approaches for chronic pain management.